A molybdenum sulfo-oxide/cobalt oxysulfide Z-scheme heterojunction catalyst for efficient photocatalytic hydrogen production and pollutant reduction. Issue 10 (14th February 2022) - Wu, Qinhan; Abdeta, Adugna Boke; Kuo, Dong-Hau; Zhang, Hanya; Lu, Qingxin; Zhang, Jubin; Zelekew, Osman Ahmed; Mosisa, Mengistu Tadesse; Lin, Jinguo; Chen, Xiaoyun
Abstract : Sulfur-doped oxide (oxysulfide)/oxygen-doped sulfide (sulfo-oxide) with a Z-scheme heterogeneous interface improves the efficiency of photocatalytic hydrogen production. Abstract : The existence of a heterojunction in the catalyst structure improves the efficiency of photocatalytic hydrogen production. The two phases of the heterojunction can be adjusted simultaneously by doping sulfur and oxygen to achieve a suitable energy band structure. Herein, we demonstrated a Mo(S, O)/Co(O, S) Z-scheme heterojunction catalyst system (abbreviated as MoCoOS) with different Co(O, S) doping amounts by a simple one-step method. Doping of different atoms in the crystal changes the energy band structure which tunes the optical, electrical, and electrochemical properties of MoCoOS. MoCoOS-2 prepared at a Co precursor content of 20 mmol performed the best at a rate of 153.4 μmol h −1 in photocatalytic hydrogen evolution, and it also showed excellent catalytic activities and good stability in reducing MO, MB, RhB, 4-NP and Cr 6+ . This efficient MoCoOS-2 catalyst can have practical applications in photocatalytic hydrogen production and catalytic reduction of chemical pollutants.